Rivera - Kettenmann, Andrea (Taschen, 2015)
An artist is born -- Apprentice years in Europe -- The Mural: a post-revolutionary ideal -- Communist ideology for capitalist clients -- From recognition to renown -- Dream of peace and unity: the last journey -- Diego Rivera 1886-1957 life and work